Nottingham - Makaryk, Nathan (Sydney : Bantam, 2019)
Nottingham mixes history and myth into a compelling novel of power, ambition and heroism - one that twists and turns far beyond the traditional tale of Sherwood Forest's iconic thief. England, 1191. King Richard is half a world away, fighting for God and his own ambition. Back home, the country languishes, bankrupt and on the verge of anarchy. People with power are running unchecked. People without are growing angry. And in Nottingham, the largest and wealthiest shire in England, a dangerously passive sheriff seems intent on doing nothing. As the leaves turn gold in the Sherwood Forest, the lives of six people - Robin and William, soldiers running from their pasts; Marian, a noblewoman working for change; Arable, a servant girl with a secret; Guy of Gisbourne, a beleaguered guard captain; and Elena Gamwell, a brash, ambitious thief - become intertwined. And a strange story begins to spread.
Also available in elelctronic book form.
Keywords: Robin Hood (Legendary character) -- Fiction; Historical fiction; Sherwood Forest (England) -- Fiction; Great Britain -- History -- Richard I, 1189-1199 -- Fiction